The Effect of Emotional Labor and Emotional Exhaustion on Turnover Intention, Mediated by Job Satisfaction in the Healthcare Sector in Ubud, Bali - I Gusti Ayu Agung Silvia Wulan Dewi; Liem Bambang Sugiyanto; Fahrul Riza; Romauli Nainggolan; Ida Bagus Gde Agung Yoga Pramana (Jurnal Ilmiah Akuntansi & Bisnis, 2026)
Hospitals are service-oriented industries that involve intensive interaction between staff and patients. Emotional exhaustion resulting from the demands of constant interaction can reduce organisational commitment, which in turn drives staff to consider leaving their jobs. This study aims to analyse the influence of Emotional Labour and Emotional Exhaustion on Turnover Intention, with Job Satisfaction acting as a mediating variable. The method used in this study is quantitative, employing SEM-PLS data analysis. The study sample comprised 107 respondents, consisting entirely of non-medical staff. Data collection utilised a questionnaire distributed via Google Forms. The results of this study indicate that job satisfaction is the key factor in explaining the relationship between Emotional Labour, Emotional Exhaustion, and Turnover Intention. Job satisfaction is a factor contributing to high turnover intentions in healthcare organisations operating in the service sector, such as hospitals. The practical implications of these findings can be utilised by healthcare organisations in hospital management to formulate more effective employee retention strategies.